ISTINBATH HUKUM MAHAR NON MATERI (JASA) PERSPEKTIF IMAM ABU HANIFAH DAN IMAM SYAFI’I. - nur hadi (IAIN Purwokerto, 2019)
The research aims to find out the opinion of Imam Abu Hanifah and Imam Syafi'i and the similarities and also differences in determining the Non Material Dowry Law (services). This type of research is literature. The primary data sources are the books of the two priests, as well as the source of the secondary books of fiqh and books relating to research. The data was analyzed using descriptive, deductive, inductive, and comparative methods. The result: Disagreements between the two Imam madzhab were due to differences in law enforcement. Imam Hanafi in determining the status of Non Material Dowry Law (services) uses the surah al-Nisa '24, al-Baihaqi hadith and he put forward qiyas, that is limiting the dowry to at least ten dirhams, and dowry in the form of Qur'anic teaching to candidates of wife is unauthorized. Imam Syafi'i using the surah al-Nisa '24 and al-Bukhari's hadith, which does not limit the lowest dowry, such as sewing clothes or teaching Al-Quran to his wife and any benefits that are owned and lawful in price and having the value of simplicity at the dowry is preferred, he looked at the sunnah, that it is not excessive if it is legitimately used as a dowry, looking at zhahir verses and hadith. Keywords: Non-Material Dowry Law, Comparative Study.